Rekonstruksi Pendistribusian Produk UMKM Guna Percepatan Daya Saing Menuju Masyarakat Ekonomi ASEAN - Santoso, Dimas Bagus; Fikriyah, Alifatul; Sholihah, Jamilatus (Lentera Hukum, 2015)
Micro, Small, and Medium Enterprises (MSMEs) are a form of business consisting of micro, small and medium enterprises. The state is to increase national economic development by optimizing the existence of MSMEs as local businesses. UMKM can become the main guard in facing global competition, especially in the competition of the ASEAN Economic Community (AEC). The implementation of the AEC which opens trade flows freely as possible can provide opportunities for MSMEs to distribute their products freely, but the distribution conditions of MSME products are currently constrained by traditional and hereditary work patterns because MSMEs only focus on making products without mapping market strategies. The current distribution is still experiencing several problems, mainly related to weaknesses in obtaining market opportunities and expanding market share and the limitations of cooperative business networks between small entrepreneurs. Therefore, it is necessary to reconstruct the distribution of UMKM products to build MSMEs into the independent, quality, and highly competitive business actors. The reconstruction was realized based on the theory of legal systems according to L. Friedman, namely legal substance, legal structure, and legal culture. Legal substance is manifested by the revision of regulations to accommodate the distribution reconstruction. The legal structure is embodied by the formation of the Coordination Agency for the Distribution of Business Products, and a legal culture which is manifested by the formation of a new culture in the process of distributing UMKM products. KEYWORDS: MSMEs, Economic Competitiveness, ASEAN Economic Community